When the Ark comes to town - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Millions of people in ACP countries live from livestock farming in towns and their peripheries. Their activities have to be monitored to protect public health and the environment. The urban livestock farming sector is coming in from the margins, and...